Molecular diversity in rice genotypes using microsatellite and SUB1 gene specific markers: Molecular diversity in rice - Satyendra; Rahul Singh; Sweta Sinha; Mankesh Kumar; Anand Kumar; Suresh Prasad Singh; Prabhash Kumar Singh (ORYZA-An International Journal of Rice, 2024)
The present study was aimed to reveal genetic diversity in rice genotypes for important agronomic traits and submergence tolerance using microsatellite markers and SUB1 specific genic markers. In this context, we used a set of 27 microsatellite markers and gene specific markers for estimation purpose. The genotypes were of broad genetic base and some of them showed differential tolerance to complete flash flood submergence. Total number of alleles and Polymorphism Information Content (PIC) value were calculated for different markers. A total of 55 alleles were detected across the 28 genotypes. On an average, two to three alleles per locus were found to be produced. The range of PIC values was found to be varying from 0.07 to 0.37, with an average of 0.27 per locus. Based on molecular information generated by polymorphic SSR markers, 28 genotypes were grouped in five different clusters. Maximum twelve genotypes were grouped in cluster II while minimum one genotype was grouped in cluster V. Among the 28 genotypes, the highest dissimilarity index was observed between Rajendra Suwasini and RYC-743; and between Sabour Surbhit and RYC-743 while the lowest dissimilarity index was observed between RAU 3001 and Vaidehi. SUB1 specific makers amplified similar size of allele for RYC 743, Purnendu, Swarna Sub-1, and IR 96321-315-402-B-1 revealing the presence of SUB1 in these genotypes. Interestingly, some of the genotypes showed good amount of submergence tolerance but could not amplify for SUB1 specific makers.